Evaluation of Numerical Methods for Predicting the Energy Performance of Windows - Anatoliy M. Pavlenko; Karolina Sadko (Energies, 2023)
Windows are important structural components that determine the energy efficiency of buildings. A significant parameter in windows technology is the overall heat transfer coefficient, U. This paper analyzes the methods of numerical determination of the U-value, including for windows that use passive technologies to improve thermal performance. The analysis was intended to evaluate the heat flux and temperature distribution across glazed surfaces and the accuracy of traditional approaches to the determination of heat loss through window structures. The results were obtained using the heat flux measurement method described in the international standard ISO 9869-1:2014. The paper shows that the non-uniformity of the heat flux density on a window surface can be as high as 60%, which in turn generates an error in the calculations based on stationary heat transfer conditions.